Uji Ekstrak Daun Binahong ( Anredera cordifolia Steen.) Terhadap kadar Gula Darah Pada Tikus Putih Jantan Galur Wistar ( Rattus norvegicus) yang Diinduksi Sukrosa - Makalalag, Indri Wirasuasty; Wullur, Adeanne; wiyono, Weny (PHARMACON, 2013)
ABSTRACT The objective of this research were tostudy the effect of Binahong leaf extract (Anredera cordifolia Steen.) on blood glucose content of white male Wistar rats (Rattus norvegicus) induced with sucrose.  This research using Randomized Controlled Group Design (RAL).The subjects in these research were 15 mices which divided into 3 groups, namely a negative control group (aquadest), a positive control group (Glucobay4,5 mg/KgBB) and treatments groupusing crude extract of Binahong leaf 1,8 g/KgBB.  Data were obtained after blood glucose examination at 15, 30, 60, and 120 minutes treatment. Data were analyzed using ANOVA and LSD to compare the effect of treatment. Statistical analysis shows that there are significant effect between a negative control group and treatment group, a negative control group and a positive control group, but did not show differences between treatment group and a positive control group.  The conclusion is Binahong leaf extract possess activity to decrease blood glucose content of white male wistar induced with sucrose.   Keywords: Anredera cordifolia Steen.,Extract, blood glucose content